Komunikasi Sosial dalam Mendorong Penetapan Kebijakan Publik HIV/AIDS - Hadi Suprapto Arifin; Ditha Prasanti; Ikhsan Fuady (FISIP Universitas Atma Jaya Yogyakarta, 2018)
This research studies about the use of social communication process in encouraging public policy on HIV/AIDS prevention in Pangandaran, West Java, Indonesia. It is a qualitative research with action research as the method. The result indicates the existence of social communication form such as direct social communication, social communication using mass media, and functional social communication involving elements of social communication. The social communication process is seen through the coordination of local government with several related agencies and foundations who care about HIV/AIDS. This encourages Local Government of Pangandaran in determining local regulation on HIV/AIDS prevention in Pangandaran tourism area.